Assessment of Heavy Metals in Dust Fall in Kampar - Chew, Min Jie (2015)
The aim of this study was to determine the concentration and composition of dust fall in Kampar, Malaysia as an abandoned tin mining area from mid-February to midJune 2015. The dust fall samples were collected in the form of rainwater, which was a combination of dry and wet deposition, by using polyethylene bottles on a monthly basis so as to determine the concentration of undissolved solids, dissolved solids and total solids from eight monitoring stations. The concentration of heavy metals (B, Al, Cr, Mn, Fe, Ni, Zn, As, Cd, Sn, Hg and Pb) was analyzed using an inductively coupled plasmamass spectrometer (ICP-MS). The results showed that the average concentration of total solids around Kampar were 20.39 ± 2.60 mg/m2 /day, which was below the value of 133 mg/m2 /day as recommended by the Malaysian Department of the Environment. Zn, As and Al were recorded as the dominant heavy metals in rainwater followed by B, Fe, Cr, Pb, Ni, Mn, Hg, Sn and Cd. However, toxic heavy metals which include As, Hg and Pb were found to be exceeded the Drinking Water Quality Standard as recommended by Malaysia and USEPA. The enrichment factors (EF) revealed that the source of the heavy metals in the rainwater was anthropogenic, except for Mn and Fe. This study suggests that former mining activities and anthropogenic activities such as motor vehicles and construction activities were the main sources of dust fall in the study areas.